The Realization of Thematic Progression in Background of Study Section Written by Undergraduate Students at Tidar University - Akhmad Zamroni; Sri Wuli Fitriati; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
This study aimed to find out the realization of thematic progression pattern applied in background of the study section in final projects written by undergraduate students and evaluate the quality of thematic progression used by the students. The objective of this study were to explain the realization of thematic progression pattern used and to explain the quality of thematic progression used by the students. The design of this study used qualitative approach descriptive study especially in discourse studies. This research used fifteen background of the study section as the source of the data. The researcher used documentation and interview as the instrument by using the theory proposed by Bloor & Bloor (2024). This study revealed that the students primarily used linear theme pattern to organized their writing with 310 times. They also applied linear theme pattern with 202 times. While, split rheme pattern applied by students with 32 times. The last is derived theme pattern applied by students with 15 times. In addition, the result of the quality of background of the study section are almost students applied thematic progression in fair level. To sum up the realization and the quality of thematic progression used by the students, they have practically applied the various thematic progression and made their background of the study section are coherence.